ANALYSIS AND EVALUATION OF THE ACCURACY OF METHODS FOR CALCULATING THE DENSITY OF CHANNELS AND THE COMBINED AREA OF THE CONTACT SURFACE OF LUBRICATION-FREE PISTON SEALS - TYMOSHCHUK, Oleksandr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
On the basis of the theory of stochastic fields, methods of calculating the tightness of the deadly piston seals were developed to perform the engineering methods of calculations intended for the field of mechanical engineering. The dependence of the channel probability density on the set of contact conditions was investigated based on the theory of stochastic fields. Analysis of research shows that the dependence of the channel probability density on the complex of contact conditions is extreme. This result is explained by the influence of the process of merging the contact spots during the loading process. To determine the density of the channels, an exact formula is derived that depends on the spectral moments and the effective level of deformation. On the basis of the exact formula, the calculation formula of the probability density of the channels was obtained for carrying out engineering calculations of the tightness of lubrication-free piston seals. The values calculated by the exact and estimated channel density formulas differ by no more than 0.0045.The exact formula of the specific surface area of the joint washed by the working medium is derived and investigated.The dependence of the combined surface area of the joint washed by the medium on the set of contact conditions was investigated. Values of quantities calculated according to exact and calculation formulas of the specific surface area of the joint washed by the medium differ by no more than 6.1%.
Keywords: contact; interconnected surfaces; density of probability of heights of depressions; the density of the heights of the vertices; the specific area of the rough surface; the specific surface area of the contact joint, which is washed by the working environment; tightness of channels; complex of contact conditions; relative actual contact area; tightness of the penetrating piston seals; the specific surface area of the joint washed by the environment; stochastic field theory